Functions and Intuitionistic Fuzzy Volterra Spaces (Journal of Informatics and Mathematical Sciences, 2017)
The focus of this paper is to investigate results of functions that preserve intuitionistic fuzzy Volterra spaces in the context of images and preimages.
Keywords: Intuitionistic fuzzy \(G_δ\) set; Somewhat intuitionistic fuzzy Volterra function; Intuitionistic fuzzy dense; somewhat intuitionistic fuzzy continuous; Somewhat intuitionistic fuzzy open